Advancement on optical methods in stress dead-zone characterisation and SIF evaluation. (October 2022) - Farahani, Behzad V.; Direito, Frederico; Sousa, Pedro J.; Melo, Francisco Q.; Tavares, Paulo J.; Infante, Virginia; Moreira, Pedro M.G.P.
Highlights: Stress dead zone concept was assessed by advanced high-resolution optical techniques. Electronic Speckle Pattern Interferometry (ESPI) was employed to measure the crack. Digital Image Correlation (DIC) was used for comparable experimental solution. Stress dead zone was geometrically evaluated by ESPI and DIC. Stress intensity factor was calculated from stress dead zone and optical methods. Abstract: The work described in this paper is a study of the stress dead zone (SDZ) concept with advanced full-field optical methods. The SDZ is a region located around the fatigue crack flanks, adding a negligible contribution to internal stresses on the global deformation energy calculation. In the analytical modelling, this area can be removed from the structural member, resulting in a geometry simplification, and in the possibility of using analytical formulations in the Stress Intensity Factor (SIF) calculation associated to the existing fatigue crack. In a fatigue-testing program, aluminium middle tension (MT) specimens were prepared and then subjected to a cyclic fatigue loading, in order to generate different crack lengths for each specimen. Then, the fatigued specimens are monotonically tested under a uniaxial tensile loading to assess the SDZ concept. The experimental data is collected and analysed through two full-field high-resolution optical techniques with different system resolutions, Digital Image Correlation (DIC), and Electronic Speckle Pattern Interferometry (ESPI). As a result, the SDZ is geometrically characterized through a set of mathematical formulations based on the compliance function for the studied specimens, and is experimentally identified through deformation fields obtained from both DIC and ESPI techniques. The obtained results from both high-resolution methods verify the validity of the concept and demonstrate that it can be used to simplify the analysis.